ON THE CONCEPT OF PRINTED HERITAGE AND DISPERSION OF THE LITHUANIAN PRINTED EXILE HERITAGE - BRAZIŪNIENĖ, ALMA (Knygotyra, 2015)
On the basis of the works by various foreign and Lithuanian authors, the article deals with the concept of printed heritage and its place within the wider system of both tangible and intangible cultural heritage. The Lithuanian printed exile heritage is a part of the Lithuanian printed heritage. Printed exile materials are stored in the major Lithuanian libraries, such as National Martynas Mažvydas Library, Vilnius University Library, the Library of Lithuanian Academy of Science, as well as in main museums of Lithuania. The article discussses several issues related to the assimilation of Lithuanian printed exile heritage. What is the status of the printed exile heritage compared to other types of cultural heritage? Should it be treated in a special way or as an integral part of Lithuanian printed heritage? What concrete steps should be taken to make it more accessible? The main challenge, in the author’s view, is to achieve the right trade-off between the integration of the printed exile heritage and preservation of its uniqueness and identity.